KAKO PRODUKTNA BERZA NOVI SAD MOŽE UTICATI NA OČUVANJE ŽIVOTNE SREDINE - Bejatović, Gordana; Pavlović, Tatjana (International Journal of Economic Practice and Policy, 2025)
Environmental protection implies a complex process of numerous interconnected elements, measures and activities, as well as analyzing and predicting the scope of future activities, all with the aim of preventing potential negative impacts, which would further threaten and degrade it (Turney et al, 2020). Dynamic changes in the international business environment have caused changes in the rules of the game on the world market (Aničić et al, 2019). The modern market imposes more and more serious demands placed on commodity exchanges in terms of connected and globalized processes of their business, then through the implementation of internationally valid standards (as an integral part of socially responsible business), which enables but also facilitates the free flow of goods on the global market. In the paper, we will consider potential actions and activities of Commodity Exchange Novi Sad, which could result not only in raising awareness, but also in concrete actions that will have results in preservation of the environment.